Does Acclimatization Have Any Impact On Primary Health Status Among Students Of Vit University, Vellore? - Ghosh, Jhimli; Ghosh, Asit Ranjan; Porchelvan, P (Asian Journal of Medical Sciences, 2013)
Objective: The present study was undertaken to determine the overall prevalence of nutritional status among young adult of VIT University, Vellore with impact of psycho-somatic changes, primary health and climate change among fresh admission. Material & Methods: Study measured data on height and weight of adults aged 17-23 years of the newly admitted students (n=157; Girls=87 & Boys=70). One commonly used indicator i.e., body mass index (BMI; kg/m2) was used to evaluate the nutritional status of subjects. Based on BMI, chronic energy deficiency (CED) and obesity were determined accordingly. Results: The mean BMI varies from 21.828 to 23.223 among girls between 17-23 years of age while 23.493 to 24.265 among boys of 17-19 years of age. The mean magnitudes of BMI are between 23.497 and 22.563 respectively among students of 17 to 23 years old. The nutritional status of 57.32% of fresher is normal with the estimated BMI while 11.46 % are suffering from under-nutrition and 31.21% are with obesity. Overall prevalence of CED was (11.3 %). Among 87 girls, 58 (67.5%) and 27.1% of 70 boys are psychologically stressed. The study has also intervened the shifting of time management and utilization before and after to VIT system. Students either gained or lost their bodyweight during the first semester of academic courses; a total of 51 students (17 girls and 34 boys) lost their weight by 1-10 kg while a total of 36 students gained weight. Conclusion: Acclimatization has brought changes among studied students those who came from distant states. Asian Journal of Medical Science, Volume-3 No-3 (2012), Page -12-19 DOI: http://dx.doi.org/10.3126/ajms.v3i3.5687